Prevalence of and risk factors for abnormal left ventricular geometrical patterns in hypertensive subjects administered irbesartan. Issue 3 (2nd January 2021) - Huang, Cheng; Huang, Yuqing; Zhong, Qi; Cai, Anping; Feng, Ying‐qing
Abstract: Background: Distinct populations differ in LVH prevalence and impaired LV geometry. Currently, the prevalence of and risk factors for LV geometric patterns in Chinese hypertensives administered irbesartan have not been specifically addressed in large studies. Methods: Totally 10, 883 patients (6623 men and 4260 women) completed the survey, including 1181 hypertensives administered irbesartan (488 males and 693 females) that were finally enrolled. Based on LVMI and RWT derived from comprehensive echocardiography, the LV geometric patterns of irbesartan‐treated hypertensive individuals were classified into four types, including the normal, concentric remodeling, and concentric and eccentric hypertrophy groups. Logistic regression analysis was applied in males and females, respectively, for determining odds ratios (ORs) and 95% confidence intervals (CIs) for various potential risk factors for abnormal LV geometrical patterns in irbesartan‐treated hypertensives. Results: The clinical and echocardiographic data differed significantly between males and females. The prevalence rates of concentric remodeling, concentric hypertrophy, and eccentric hypertrophy were 36.3%, 15.4%, and 6.1% in males, respectively, and 23.5%, 20.3%, and 23.8% in females, accordingly. Gender, daily dose of irbesartan, BMI, SBP, WtHR, and neck‐circumference were significantly associated with LV geometric patterns. After adjustment for confounding factors, risk factors for LVH and impaired LV geometry included SBP, WtHR in males, and MAU‐Cr and WtHR in females. Conclusions: LVH and impaired LV geometric patterns are more prevalent in females (67.7%) compared with that in males (57.8%) among hypertensives upon irbesartan administration. For such population, risk factors beyond elevated blood pressure may be involved in the progression of LVH and impaired LV geometric patterns in both genders. Abstract : Prevalence of and risk factors for abnormal left ventricular geometrical patterns in hypertensive subjects with irbesartan treatment.